2000
DOI: 10.1093/oxfordjournals.jbchem.a022774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Molt-Inhibiting Hormone of the American Crayfish Procambarus Clarkii, and Determination of the Location of Its Disulfide Linkages

Abstract: A molt-inhibiting hormone (Prc-MIH) of the American crayfish, Procambarus clarkii, a member of the type II CHH family, was chemically synthesized and the location of its three disulfide linkages was determined. Prc-MIH consists of 75 amino acid residues and was synthesized by a thioester method. Two peptide segments, Boc-[Cys(Acm)(7,24,27), Lys(Boc)(19)]-Prc-MIH(1-39)-SCH(2)CH(2)CO-Nle-NH(2) and H-[Cys(Acm)(40,44,53), Lys(Boc)(42,51,67)]-Prc-MIH(40-75)-NH(2), were prepared using peptides obtained via the Boc s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…The results showed that rMIH-B had three disulfide bonds connected between Cys 7 and Cys 44 , Cys 24 and Cys 40 , and Cys 27 and Cys 53 . This arrangement was identical with that of other CHHfamily peptides reported previously (Kegel et al 1989;Huberman et al 1993;Martin et al 1993;Yasuda et al 1994;Gasparini et al 1994;Aguilar et al 1995Aguilar et al , 1996Nagasawa et al 1999;Kawakami et al 2000).…”
Section: Mih-like Peptide Named Mih-b From M Japonicussupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that rMIH-B had three disulfide bonds connected between Cys 7 and Cys 44 , Cys 24 and Cys 40 , and Cys 27 and Cys 53 . This arrangement was identical with that of other CHHfamily peptides reported previously (Kegel et al 1989;Huberman et al 1993;Martin et al 1993;Yasuda et al 1994;Gasparini et al 1994;Aguilar et al 1995Aguilar et al , 1996Nagasawa et al 1999;Kawakami et al 2000).…”
Section: Mih-like Peptide Named Mih-b From M Japonicussupporting
confidence: 89%
“…10). This arrangement is identical to those of other CHH-family peptides determined thus far (Kegel et al 1989;Huberman et al 1993;Martin et al 1993;Yasuda et al 1994;Aguilar et al 1995Aguilar et al , 1996Nagasawa et al 1999;Kawakami et al 2000;Katayama et al 2001) and, therefore, it is likely that this arrangement of disulfide bonds is also the same as in the native Pej-SGP-I. These results indicate that the difference in conformation between rPej-SGP-I-OH and rPej-SGP-I-amide is caused not by the variation of disulfide bond arrangement, but by the conformational change of the C-terminal region.…”
Section: -1e Preparation Of Recombinant Chhssupporting
confidence: 83%
See 1 more Smart Citation
“…Subsequently, the beads were washed five times with blocking buffer (0.01 M phosphate buffer, pH 7.0, containing 0.1% casein, 0.4 M NaCl, 0.01 M MgCl 2 and 0.1% NaN 3 ). The primary antibody-coated beads were incubated with 150 µ l of standard synthetic Prc-MIH (Kawakami et al, 1999(Kawakami et al, , 2000Sonobe et al, 2001) solution or sample solution for 14 hr at 4°C. The beads were incubated with biotinylated secondary antibody, anti-Prc-MIH(55-75)-NH 2 IgG solution (100 ng/ml of blocking buffer), for 1.5 hr at 25°C with shaking (180 strokes/min), and then reacted with streptavidin-β-D-galactosidase conjugate (0.25 U/ml, Roche Diagnostics, Germany) for 1 hr at 25°C with shaking.…”
Section: The Sandwich-type Eiamentioning
confidence: 99%
“…[Lys (Ub) 18 ,Cys(Acm) 96,110 ]H3.1 (14) was partially purified by gel filtration (75%), after which, the Acm groups were removed. We first attempted the removal by silver acetate in an aqueous acetic acid solution, 32 but the removal of the Acm groups were not complete, even after a 24-hour reaction (data not shown). It was recently reported that a Pd catalyst could be used to efficiently remove Acm groups.…”
Section: Resultsmentioning
confidence: 99%